A novel spiral backoff mechanism for wireless sensor networks MAC protocol in smart grid system - Ahmed, Musse Mohamud; Bari, S.M. Sadakatul (IEEE, 2015)
Wireless sensor networks are considered as the enabling technology for multiple smart grid applications such as remote metering, direct load control, renewable energy integration, substation monitoring etc. The IEEE 802.15.4 standard provides a basic foundation by defining the physical and MAC layer of the low power wireless sensor network. Carrier Sense Multiple Access-Collision Avoidance (CSMA-CA) with binary exponential backoff (BEB) algorithm is used as a technique to share the common wireless medium and avoids collision among the contending sensor nodes. However, this binary exponential algorithm does not account the application of traffic characteristics that essentially negatively affects the smart grid network performances in terms of packet delivery ratio and the time delay. In this paper, a novel spiral backoff mechanism is proposed that has considered the applications of traffic type to improve the network performances. Simulation results show that proposed spiral backoff algorithm reduces the end-to-end delay and increases packet delivery ratio (PDR) for the smart grid wireless sensor networks.